(untitled) (Intent Research Scientific Journal, 2023)
Uzbek musical drama is a multidisciplinary, complex art. The production of a work in the genre of musical drama is carried out by a creative team consisting of a playwright, composer, director, conductor, concertmaster, choreographer, and artists. It should be especially noted the merits of such composers as Tokhtasin Jalilov, Georgy Mushel, Talibjon Sadykov, Yunus Rajabi, Ikrom Akbarov, Manas Leviev in the formation of professional Uzbek Musical theater. This article highlights the current problems of modern Uzbek musical drama. These problems are covered from the point of view of the actors of the musical drama.